PENGARUH BIAYA OPERASIONAL TERHADAP LABA DI UD. ROTI HELENA TELUKDALAM - FAU, SAMANOI HALOWO; Duha, Timotius; Waoma, Samalua (Balance: Jurnal Riset Akuntansi dan Bisnis, 2022)
This research aims to determine operating costs’ impact on profits in UD. Roti Helena Telukdalam. The population and sample in this study are reports of the remaining results of 8 years of effort using data interpolation methods to meet population and sample criteria. The data analysis method used is multiple linear regression analysis, where the regression model value Y = 33,152,877 +0.647X. The results of this study showed that operating expenses (X) had a significant effect on profits at UD. Roti Helena Telukdalam with a thi calculated value of 4,431>Ftabel of 1,696. This research can be concluded that operating costs have a significant effect on profits in UD. Roti Helena Telukdalam.